Impact of digital sales marketing and traditional sales marketing on the purchase decision process in the software industry - Akter Ria, Mst. Sadia (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.